(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In this article, detailed information about relevance, aim and objectives, scientific novelty, experience of EU in assessment tools of digital transformation and experience of Uzbekistan in assessment digital transformation, comparative analysis, which methods of EU can be adapted in Uzbekistan in digital transformation assessments given.